Digital Forensics and Cyber Crime Third International ICST Conference, ICDF2C 2011, Dublin, Ireland, October 26-28, 2011, Revised Selected Papers - Gladyshev, Pavel; Rogers, Marcus K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book contains a selection of thoroughly refereed and revised papers from the Third International ICST Conference on Digital Forensics and Cyber Crime, ICDF2C 2011, held October 26-28 in Dublin, Ireland. The field of digital forensics is becoming increasingly important for law enforcement, network security, and information assurance. It is a multidisciplinary area that encompasses a number of fields, including law, computer science, finance, networking, data mining, and criminal justice. The 24 papers in this volume cover a variety of topics ranging from tactics of cyber crime investigations to digital forensic education, network forensics, and the use of formal methods in digital investigations. There is a large section addressing forensics of mobile digital devices.
The Role of Perception in Age Estimation -- Internet Child Pornography, U.S. Sentencing Guidelines, and the Role of Internet Service Providers -- Law Enforcement 2.0: Regulating the Lawful Interception of Social Media -- All Bot Net: A Need for Smartphone P2P Awareness -- Results of Field Testing Mobile Phone Shielding Devices -- Windows Phone 7 from a Digital Forensics$1 (BPerspective -- Forensic Extractions of Data from the Nokia N900 -- A Strategy for Testing Metadata Based Deleted File Recovery Tools -- Finding Anomalous and Suspicious Files from Directory Metadata on a Large Corpus -- A Novel Methodology for Malware Intrusion Attack Path Reconstruction -- Performance Issues about Context-Triggered Piecewise Hashing -- Formal Parameterization of Log Synchronization Events within a Distributed Forensic Compute Cloud Database Environment -- Yahoo! Messenger Forensics on Windows Vista and Windows 7 -- Finding Forensic Information on Creating a Folder in $LogFile of NTFS -- Evaluating the Forensic Image Generator Generator.s
Keywords: Computer science; Computer network architectures; Data protection; Computer files; Information Systems; Computer Science; Systems and Data Security; e-Commerce/e-business.; Computers and Society; Management of Computing and Information Systems; Computer System Implementation; Files